Human Resource Development Research Handbook : Linking Research and Practice - Swanson, Richard A. and Holton III, Elwood F.; Swanson, Richard A., 1942-; Holton, Elwood F., 1957- (San Francisco : Berrett-Koehler, 1997)
The first book to explain the value, purposes, methods, and processes of HRD research in clear, simple language, the Human Resource Development Research Handbook gives practitioners the tools they need to stay on the leading edge of the profession. Top researchers in the field demystify the research process so HRD practitioners can transform their practice to incorporate leading-edge research. Each chapter is written in straightforward language by a leading researcher. Real-world examples clearly show how research and theory are not just for academics, but are practical tools to solve everyday problems
Foreword: The Seed of Research / Ken Melrose -- 1. HRD Research: Don't Go to Work Without It! / Richard A. Swanson -- 2. How Research Contributes to the HRD Value Chain / Michael P. Leimbach and Timothy T. Baldwin -- 3. HRD Partnerships for Integrating HRD Research and Practice / Ronald L. Jacobs -- 4. Quantitative Research Methods / Elwood F. Holton III and Michael F. Burnett -- 5. Qualitative Research Methods / Barbara L. Swanson, Karen E. Watkins and Victoria J. Marsick -- 6. Theory-Building Research Methods / Richard J. Torraco -- 7. Case Study Research Methods / Victoria J. Marsick and Karen E. Watkins -- 8. Examples of Excellent HRD Research / Gary N. McLean and Darlene Russ-Eft
"Sponsored by The Academy of Human Resource Development & The American Society for Training and Development."
Includes bibliographical references and index
Keywords: Human capital -- Research -- Methodology; Human Capital - Research - Methodology; Research Methods - Human Resource